Pulse oximetry in children: understanding and interpreting oxygen saturation - Bellsham-Revell, Hannah (Henry Stewart Talks, 2025)
Pulse oximetry in children, Oxygen saturation and desaturation, Hyperoxia test, Pre- and post-ductal saturations, Coarctation of the aorta, Treating abnormal oxygen saturation levels